The Effect of Pterygium and Pterygium Surgery on Corneal Biomechanics. (19th May 2018) - Koç, Mustafa; Yavrum, Fuat; Uzel, Mehmet Murat; Aydemir, Emre; Özülken, Kemal; Yılmazbaş, Pelin
ABSTRACT: Purpose : To evaluate the effect of pterygium and pterygium surgery on corneal biomechanics by ocular response analyzer (ORA, Reichert, USA). Methods : This study considered 68 eyes (from 34 patients with a mean age of 21.2±7.1 years) with unilateral nasal, primary pterygium (horizontal length <4 mm), and having undergone pterygium excision and conjunctival autografting. Pterygium length and area were measured from a photograph of the anterior segment using Image J program. ORA measurements were obtained before surgery and after the first month of the surgery. The measurements of the eyes with pterygium and healthy eyes were compared to evaluate the effect of pterygium. Similarly, measurements obtained before and after surgery were compared to evaluate the effect of pterygium surgery on corneal biomechanics. The correlation of the ORA measurements with the pterygium area was evaluated. Results : Mean pterygium horizontal length and area were 3.31±1.43 mm and 6.82±2.17 mm 2, respectively. There was no statistically significant difference between the eyes with and without pterygium in corneal hysteresis (CH, p =0.442), corneal resistance factor (CRF, p =0.554), corneal-compensated intraocular pressure (IOPcc, p =0.906), and Goldmann-correlated IOP (IOPg, p =0.836). All preoperative parameters decreased after surgery; however, none of them were statistically significant (CH, p =0.688; CRF, p =0.197; IOPcc, p =0.503; IOPg, p =0.231). There were no correlations between pterygium area and ORA measurements ( p >0.05). Conclusion : Pterygium <4 mm and its surgical excision did not affect corneal biomechanics. These results may be taken into account when cornea biomechanics, mainly intraocular pressure measurements, are important.